Thalamic deep brain stimulation for orthostatic tremor: A multicenter international registry. Issue 8 (20th June 2017) - Merola, Aristide; Fasano, Alfonso; Hassan, Anhar; Ostrem, Jill L.; Contarino, Maria Fiorella; Lyons, Mark; Krauss, Joachim K.; Wolf, Marc E.; Klassen, Bryan T.; van Rootselaar, Anne‐Fleur; Regidor, Ignacio; Duker, Andrew P.; et al.
Abstract: Background: We report the accumulated experience with ventral intermediate nucleus deep brain stimulation for medically refractory orthostatic tremor. Methods: Data from 17 patients were reviewed, comparing presurgical, short‐term (0‐48 months), and long‐term (≥48 months) follow‐up. The primary end point was the composite activities of daily living/instrumental activities of daily living score. Secondary end points included latency of symptoms on standing and treatment‐related complications. Results: There was a 21.6% improvement ( P  = 0.004) in the composite activities of daily living/instrumental activities of daily living score, which gradually attenuated (12.5%) in the subgroup of patients with an additional long‐term follow‐up (8 of 17). The latency of symptoms on standing significantly improved, both in the short‐term ( P  = 0.001) and in the long‐term ( P  = 0.018). Three patients obtained no/minimal benefit from the procedure. Conclusions: Deep brain stimulation of the ventral intermediate nucleus was, in general, safe and well tolerated, yielding sustained benefit in selected patients with medically refractory orthostatic tremor. © 2017 International Parkinson and Movement Disorder Society